THE USE OF FLASHCARDS AND ITS EFFECTIVENESS IN ELT: A SYSTEMATIC REVIEW - Siska Sari; Ika Intan Nurul Wahidah, Sintia Wati, Della Fadiana, Naf’an Tarihoran (CV. ADIBA AISHA AMIRA, 2024)
Flashcards are one of the tools used as a learning medium. Many school teachers have used flashcards as a medium for learning English. This article aims to conduct a systematic review of using flashcard to enhance proficiency in English Language Teaching (ELT). Using the PRISMA method, this article analyzed various previous studies relevant to the topic. The search strategy is based on the following keywords: